The characteristic features of emergency food in national level natural disaster response programs: A qualitative study - Soheyla Ainehvand; Pouran Raeissi; Hamid Ravaghi; Mohammadreza Maleki (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: One of the most important responsibilities of governments and relief agencies after each natural disaster is to provide the victims with emergency food items. This is an inevitable measure to save the lives of injured and the ones who are rescued. This is due to inadequacy and unreliability of household and local food supplies. Selection of the type of food is a concern of managers of the response management programs. The purpose of this study was to investigate the characteristics of emergency food items provided after natural disasters in Iran from the key informants' viewpoints. MATERIALS AND METHODS: To conduct this qualitative study, we interviewed 26 experts in the field of nutrition and response management in natural disasters through semi-structured interviews. Participants were selected using purposive sampling. The qualitative content analysis method was further applied to analyze the collected data. RESULTS: Analysis of interviews showed that the characteristics of emergency food provided after natural disasters should be investigated in two categories: (1) nutritional considerations and (2) functional characteristics. Nutritional considerations category comprised subcategories, namely, formulas and special foods for emergencies, food diversity, nutritional needs of different groups, food health and safety, and functional characteristics included subcategories of packaging, cultural norms, and final price. CONCLUSION: Managers, in relation to the emergency food items used after natural disasters, should consider features including emergency formulas and food, food diversification, food health and safety, packaging certificates, cultural norms, and final prices in response plans.